Accuracy of toric intraocular lens axis alignment using a 3‐dimensional computer‐guided visualization system. Issue 4 (April 2016) - de Oca, Ildamaris Montes; Kim, Eric J.; Wang, Li; Weikert, Mitchell P.; Khandelwal, Sumitra S.; Al‐Mohtaseb, Zaina; Koch, Douglas D.
Abstract : Purpose : To evaluate the accuracy of toric intraocular lens (IOL) alignment in femtosecond laser–assisted cataract surgery using the Truevision 3‐dimensional (3‐D) computer‐guided visualization system compared with a manual marking method. Setting : Cullen Eye Institute, Baylor College of Medicine, Houston, Texas, USA. Design : Retrospective comparative case series. Methods : Preoperatively, all patients had corneal topography measurements with a color light‐emitting diode topographer. The 3‐D system used the anterior keratometry values to create an optimized plan for the toric IOL alignment. Intrastromal marks were created by the femtosecond laser at the intended toric meridian, guided by manual ink marks placed at the 3 o'clock and 9 o'clock limbus with the patient sitting upright. Intraoperatively, the 3‐D system was used to align the IOL and measure the angular position of the femtosecond marks relative to the IOL meridian. Three weeks postoperatively, the manifest refraction, corrected distance visual acuity, and toric IOL alignment were recorded. Results : The mean 3‐D imaging error was −0.58 degrees ± 3.90 (SD) (range −9 to 5 degrees), and the mean manual ink error was −0.27 ± 3.65 degrees (range −8 to 5 degrees); neither was statistically significantly different from zero ( P = .28 and P = .76, respectively). The mean absolute errors were 2.96 ± 2.54 degrees and 2.88 ± 2.18 degrees, respectively. Conclusion : The 3‐D computer‐guided system and manual marking combined with femtosecond laser marks were similar in accuracy for toric alignment. Financial Disclosures : Dr. Wang received research support from Ziemer USA, Inc. Dr. Weikert is a consultant to Ziemer USA, Inc. Dr. Koch is a consultant to Alcon Laboratories, Inc., and Abbott Medical Optics, Inc., and received research support from Ziemer USA, Inc., i‐Optics Corp, and Truevision Systems. None of the other authors has a financial or proprietary interest in any material or method mentioned.